2016
DOI: 10.1097/igc.0000000000000641
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Power Doppler Ultrasound for Predicting Response and Local Recurrence After Concomitant Chemoradiation Therapy for Locally Advanced Carcinoma of the Cervix

Abstract: A single 3D-PDUS assessment of tumor size and vascularization before treatment seems to be of limited value for predicting tumor response to chemoradiation therapy and for predicting tumor recurrence in women with locally advanced carcinoma of the cervix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…In these studies, the same US system was used and 4D view was used for analysis so the results are comparable. Our results are further confirmed by Alcazars findings on the uselessness of 3D-PD indices to predict recurrence after RCT in patients with locally advanced disease (130). Summarizing the published evidence, there is nothing to support the value of 3D-PD indices as a predictor for finding lymph node metastases or for monitoring therapeutic response in patients with cervical cancer.…”
Section: Lymph Nodessupporting
confidence: 83%
See 1 more Smart Citation
“…In these studies, the same US system was used and 4D view was used for analysis so the results are comparable. Our results are further confirmed by Alcazars findings on the uselessness of 3D-PD indices to predict recurrence after RCT in patients with locally advanced disease (130). Summarizing the published evidence, there is nothing to support the value of 3D-PD indices as a predictor for finding lymph node metastases or for monitoring therapeutic response in patients with cervical cancer.…”
Section: Lymph Nodessupporting
confidence: 83%
“…Research on 3D US and cervical cancer has focused as well on the possible predictive value for patients that are subject to NACT before surgery or primary RCT with negative results. FI was suggested as a predictive marker for NACT responders, (129) however, neither in the prospective PRICE study nor another smaller study were 3D vascular indices found useful to monitor response to NACT or RCT in patients with advanced disease (121,130).…”
Section: Three Dimensional Ultrasonography (3d)mentioning
confidence: 99%
“…In contrast, in the present study we analyzed ultrasound parameters only in patients undergoing neoadjuvant chemoradiation and we performed the examinations before, after and during treatment. Furthermore, while some previous studies assessed the performance of ultrasound in predicting tumor response, including tumor volume and vascular indices, to chemo‐ or chemoradiation therapy, their results were controversial. Some of them analyzed a very small sample size; others assessed only the clinical response without investigating the pathological data; and others included patients treated with neoadjuvant chemotherapy rather than chemoradiation.…”
Section: Discussionmentioning
confidence: 99%
“…There are few data in the literature assessing the role of ultrasound examination in the evaluation of tumor behavior during neoadjuvant treatment. The use of two‐dimensional (2D) ultrasound and three‐dimensional (3D) power Doppler, as well as contrast enhancement using SonoVue (sulphur hexafluoride microbubbles), has been investigated in cervical cancer, but their ability to predict pathological response in locally advanced cervical cancer has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Alcazar et al [24] observed that those tumours with pathological CR had a lower mean number of vessels (3.3 vs. 5.3, p = 0.01), lower tumour vascular density (0.1 vs. 1.1, p = 0.05) and higher resistive index (0.41 vs. 0.29, p = 0.03). No differences were found in maximum peak systolic velocity.…”
Section: Discussionmentioning
confidence: 99%